LITERATURE IN PAINTING / PAINTING IN LITERATURE: चित्रकला में साहित्य/साहित्य में चित्रकला - Joshi, Shobhana (International Journal of Research -GRANTHAALAYAH, 2019)
English : The world is pictorial, it is also a movie. "Who is this painter"! Do not know! But a small part of the universe is born in the middle of these pictures and movies, it is time-consuming. One watches these movies during the movement of breaths and stops. This which he sees, passes through the camera of his eyes and is printed in the mind and heart. He is restless. Let me share that print. A hieroglyph of this sharing from the rest. The script rang, the pictures were painted, the colors were unrefined. Manas became fertile, art enriched by imagination. Art grew to vibrancy from the sentiments of human beings progressed by primitive barbarism. The infinite beauty of the parallel vision of creation embodied dance art, singing art with Prabhavishnuta. The instruments were unmodified. When the replica of nature was found to be a sound form, the concrete shape from the soil and stone was found in the form of "sculpture". Hindi : सृष्टि चित्रलिखित सी है, चलचित्र भी है। ’’ये कौन चित्रकार है’’! पता नहीं! पर सृष्टि का एक क्षुद्र हिस्सा भर मनुष्य इन चित्रों-चलचित्रों के बीच ही जनमता है, काल-कवलित होता है। सांसों के आने-जाने और रूक जाने की अवधि में इन चलचित्रों को देखता है। यह जो वह देखता है, उसकी आँखों के कैमरे से गुजरकर दिल-दिमाग में छपता है। उसे बैचेनी होती है। उस छपे को साझा करूँ। इस साझा करने की बैचेनी से जनमी चित्रलिपि। लिपि की बेल फैली, चित्र रचे चितेरों ने, रंग अविष्कृत हुए। मानस उर्वर हुआ, कल्पना से कला समृद्ध हुई। आदिम बर्बरता से आगे बढ़े मनुष्य के भावों से कला को स्पन्दन मिला। सृष्टि के समानांतर दृष्टि के अपरिमित सौंदर्य ने प्रभविष्णुता के साथ नृत्य कला, गायन कला को मूर्त्त किया। वाद्य अविष्कृत हुए। प्रकृति की प्रतिकृति ध्वनि रूप पा गयी तो मिट्‌टी और पत्थर से ठोस आकार ’’मूर्तिकला’’ रूप में मिला।